Adapting Nephrology Training Curriculum in the Era of COVID-19. (February 2021) - Cunningham, Amanda; Hung, Wayne; Levin, Adeera; Jamal, Abeed
Purpose of review: The COVID-19 pandemic has widespread implications not only for clinical practice but also for academic medicine and postgraduate training. The need to promote physical distancing and flexibility within our department has generated important revisions to the core curriculum for the Adult Nephrology Training Program in Vancouver, Canada. Sources of information: We reviewed available educational resources and objectives to develop curricular adaptations informed by staff and trainee feedback. Methods: Many facets of the program including clinical rotations, scholarly activities, evaluation, and wellness have been impacted, and thus revised for online delivery where possible. Trainees have personalized a learning plan based on individual goals and supplemented by a list of internet-based resources for independent review. Changes in learning objectives and methods for specific rotations have occurred and are described. Ongoing evaluation will be undertaken. Key findings: Curriculum adaptation in the era of COVID-19 is necessary to ensure ongoing high-quality education for future nephrologists. We describe existing changes to formal training in British Columbia (BC), which will be tailored as the pandemic evolves, and anticipate them to have lasting impact on the way we structure training programs in the future. Standardization and harmonization of modified curriculum may be possible across Canada with sharing of these learnings. Limitations: Formal evaluation of these changes in terms of knowledge acquisition and examination performance has not yet been undertaken. Next steps will include assessing and documenting the impact of this curricular transformation to further optimize scheduling, educational yield, and trainee wellness.